(untitled) (AmeriQuests, 2006)
This article reflects upon the approach that Chomsky takes to a broad array of fields and work, and the "effect" that he has, as a thinker and a catalyst, upon a broad array of people within and beyond the ivory tower. Some of the central themes of Chomsky’s work are herein elucidated, alongside of some key events which have marked him, and his many effects, across the spectrum of activists and intellectuals who look to him for guidance or else as a figure to be reviled and attacked.